The Influence Of Digital Leadership And Digital Collaboration On The Digital Skill Of Manufacturing Managers In Tangerang - Ali Zaenal Abidin (Universitas Dharma Wacana, 2022)
Inequality in terms of digital skills is a challenge faced by organizations, both companies and governments to ensure productivity and effectiveness in working from home during Covid-19. The development of digital skills is an important factor that this article tries to discuss. Are the digital skills of employees who do WFH influenced more by the digital leadership of their supervisors or by the digital collaboration they do in their work teams? Empirical research that is cross sectional and involves 160 Manufatur Managers in Tangerang as respondents. Collecting data using an online-questionnaire with a convenience approach and snowballing as a sampling method. The data obtained were analyzed using structural equation modeling based on partial least squares in the format of first order constructs. The results of statistical hypothesis testing explain that digital skills are significantly influenced by digital collaboration and digital collaboration is influenced by digital leadership. Digital leadership has an indirect effect on digital skills. Supervisor leadership during the COVID-19 period should be more directed to encourage the development of digital collaboration so that through this digital skills develop